2017
DOI: 10.1186/s12889-017-4071-8
|View full text |Cite
|
Sign up to set email alerts
|

Trends and causes of maternal mortality in Ethiopia during 1990–2013: findings from the Global Burden of Diseases study 2013

Abstract: BackgroundMaternal mortality is noticeably high in sub-Saharan African countries including Ethiopia. Continuous nationwide systematic evaluation and assessment of the problem helps to design appropriate policy and strategy in Ethiopia. This study aimed to investigate the trends and causes of maternal mortality in Ethiopia between 1990 and 2013.MethodsWe used the Global Burden of Diseases and Risk factors (GBD) Study 2013 data that was collected from multiple sources at national and subnational levels. Spatio-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
134
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(147 citation statements)
references
References 38 publications
7
134
1
1
Order By: Relevance
“…Other causes were complications of abortus (%19.6), maternal hemorrhage (%12.2), hypertensive diseases (%10.3), maternal sepsis and infections (%9.6), HIV/AIDS (%0.5). In the same study, when the maternal mortality due to bleeding was examined according to years, early postpartum hemorrhages were found to be the main mortality cause, although antepartum, intrapartum, early postpartum and late postpartum bleeding rates decreased over the years (12). When the causes of mortality in our study were examined, it was found that the most frequent death was direct death (58%), as stated in the literature.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Other causes were complications of abortus (%19.6), maternal hemorrhage (%12.2), hypertensive diseases (%10.3), maternal sepsis and infections (%9.6), HIV/AIDS (%0.5). In the same study, when the maternal mortality due to bleeding was examined according to years, early postpartum hemorrhages were found to be the main mortality cause, although antepartum, intrapartum, early postpartum and late postpartum bleeding rates decreased over the years (12). When the causes of mortality in our study were examined, it was found that the most frequent death was direct death (58%), as stated in the literature.…”
Section: Discussionsupporting
confidence: 51%
“…53.6% (37) had a cesarean delivery, 27.5% (19) had vaginal delivery, 1.4% (1) had abortion and 17.4% (12) had died before the end of pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…The high maternal mortality rate due to complications of unsafe abortion framed the conversation of legal reform. In 2005, Ethiopia's maternal mortality ratio, although declining, was 687 deaths per 100 000 live births, with estimates at the time attributing 32% of maternal mortality to complications of unsafe abortion; later estimates would range between 19.6% and 31% . In this context, a movement developed across the medical, political, and women's rights communities to reduce maternal mortality and fulfil the rights enumerated by the new Constitution.…”
Section: Contextmentioning
confidence: 99%
“…Obstetric hemorrhage, hypertension, abortion, sepsis, HIV, preexisting medical disorders, and other indirect causes like anemia are the main causes of maternal mortality both globally and in Ethiopia [2,[4][5][6][7][8][9][10][11]. These causes of death are preventable with proven cost-effective interventions.…”
Section: Introductionmentioning
confidence: 99%